Reimagining Education: Artificial Intelligence and the Transformation of Learning Paradigm - Setiawan, Rahmat; Nurbani, Armelia Nungki; Putri, Felicia Arya Dwi; Ningsih, Retno Ayu; Diyawan, Nur Avita Ayu (English Language in Focus (ELIF), 2024)
This research aims to reveal the educational paradigm shift caused by artificial intelligence. The theoretical frameworks in this study are Artificial Intelligence and English Language Teaching. The research methodology used case study qualitative. The data used in this research consists of statements taken from the Forum Group Discussion. The data source consisted of FGD transcripts by three English teachers from a favorite high school in Surabaya. The data collection technique used focus group discussion. The analytical approach used thematic analysis. From the FGDs conducted, three axes of answers were found. The first is related to the consequences of artificial intelligence in changing the educational paradigm through tasks given to students. There are three things in giving assignments, 1) A shift from assigning tasks based on Lower Order Thinking Skills to Higher Order Thinking Skills. 2) A shift from directive assignments to reasoning or explanation and 3) Giving tasks that are theoretical to practice. Second, the learning process reflects significant changes. There are two main reasons why the learning process can cause significant shifts. 1) The shift from teacher center to student center and 2) The change from learning using traditional methods to using technology. Third, the utilization of artificial intelligence in learning purposes also reflects a very important phenomenon. There are two main reasons in learning. 1) The change from knowledge mastery to the application of knowledge to solve problems and 2) A paradigm shift from simply answering questions to developing critical and creative thinking skills.